A Tribute to Freddie R. Lamm - D. Rogers; J. Aguilar; A. R. Tomlinson (Kansas Agricultural Experiment Station Research Reports, 2022)
Freddie Lamm, who positively impacted many through his life and career, passed away on May 26, 2022. Kansas State University and the agricultural irrigation research community lost a great contributor to their field. Lamm was the research irrigation engineer at the Northwest Research-Extension Center in Colby, Kansas. He passed away sooner than his family, friends, and colleagues were ready for—before his planned retirement from his remarkable career. View the PDF linked to the right-hand column to learn more about his legacy.
Keywords: Freddie Lamm; irrigation; Kansas State University irrigation